Synergistic Effect of Metagenome‐Derived Starch‐Degrading Enzymes on Quality of Functional Bread with Antioxidant Activity. (29th July 2021) - Sadeghian Motahar, Seyedeh Fatemeh; Salami, Maryam; Ariaeenejad, Shohreh; Emam‐Djomeh, Zahra; Sheykh Abdollahzadeh Mamaghani, Atefeh; Kavousi, Kaveh; Moghadam, Maryam; Hosseini Salekdeh, Ghasem
Abstract: Starch‐degrading enzymes have gained particular importance in recent decades due to their crucial role in numerous industrial applications especially, in the bakery industry. In this study, a novel thermostable pullulanase (PersiPul1) is screened from the metagenomic data for improving the quality of functional bread. The novel PersiPul1 is active over a wide range of temperature (30–80 °C) and pH (4–9) and exhibits high thermal stability, retaining 58.70% of activity at 80 °C. A cocktail of thermostable pullulanase and α‐amylase (PersiPul1and PersiAmy2) is developed to be used in bread fortified with quinoa protein ( Chenopodium quinoa  Willd). The bread fortified with 7% quinoa protein isolate possess the highest reducing power and ABTS (73.64%) and DPPH (72.27%) radical scavenging activities. The addition of the enzyme mixture decreases the hardness and chewiness of the bread. The porosity, specific volume, and browning index of bread with pullulanase and α‐amylase are higher than control. Also, sensory analysis of the functional bread reveals higher scores in the presence of enzymes. Based on the results, the novel starch‐degrading enzyme cocktail is a promising alternative for improving the physical and sensory characteristics of the antioxidant bread enriched with quinoa protein isolate to be used in the bakery industry as a potential bio‐additive. Abstract : Starch‐degrading enzymes have gained particular importance in the bakery industry. In this regard, a novel metagenomic‐derived thermostable pullulanase (PersiPul1) is identified that is stable in harsh conditions. To improving the pullulanase function, it is combined with the thermostable α‐amylase. A cocktail is developed in functional bread formulation. The final product enables enhanced antioxidant activity, physical and sensory properties of the bread.